POROUS PLASTIC MATRIX TABLETS OF LEVETIRACETAM FOR ZERO-ORDER CONTROLLED RELEASE: DEVELOPMENT AND FORMULATION OPTIMIZATION - PARIMI, RAVI; VADAPALLI, RAMA RAO; PRAVALLIKA, K. E. (International Journal of Applied Pharmaceutics, 2021)
Objective: The prior objective of the current research work was to develop once-daily levetiracetam extended/controlled-release tablets having zero-order release kinetics with the plastic matrix as the release retarding element. For a high water-soluble drug, the formulation of a dosage form so as to have an extended drug release has always been a difficult task. Methods: In the current work, levetiracetam which is a highly soluble drug was taken as the model drug for which extended-release matrix tablets were developed using varied plastic polymers like Polyvinyl acetate (PVAc), Polyvinyl chloride (PVC), Eudragit RSPO and Eudragit RLPO. PVP was considered as a pore-forming agent and PEG 6000 was taken as a water regulating agent. The porous plastic matrix tablets were prepared by embedding the drug in solvent-activated polymer dispersion followed by drying, sieving, mixing with other excipients and finally compressed. Including physical characterization studies and drug release studies, the tablets were subjected to SEM studies before and after the dissolution studies to analyze the effect of the pore former. Results: Pre-compression mixtures exhibited good packageability of 81-92% and hence the compressed tablets were strong enough with good tensile strength in the range of 0.78–0.90 N/mm2. Drug release study results showed that the drug release was controlled for a period of 12–24h. PVAc had shown better controlled-release among all the plastic polymers taken. PEG 6000 in combination with PVP produced the desired zero-order drug release. Conclusion: The levetiracetam porous plastic matrix tablets were developed with zero-order drug release that was effectively controlled for 24hr.